THE IMPLEMENTATION OF BLENDED LEARNING IN EFL CLASSROOM AT SMA NEGERI 4 SELAYAR - Ika Ridayanti; Abd. Halim; Fatimah Hidayahni Amin (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This research was conducted to find out the implementation of blended learning in the EFL classroom. This research aims (1) to investigate the advantages and disadvantages of blended learning in an EFL classroom. (2) to know about the difficulties are teachers and students are communicating in blended learning. (3) to learn the way teachers and students solve the difficulties in blended learning. The researcher conducted this research at SMA Negeri 4 Selayar. The method of this research was descriptive qualitative research. The subjects of this research were fifteen students and two English teachers from SMA Negeri 4 Selayar. The researcher used classroom observation and interviews as the research instrument. It reveals and explains the implementation in the EFL classroom, limited facilities and infrastructure and the use of online and network applications are important factors. Researchers see that the application of blended learning in SMA Negeri 4 Selayar in its application is very relevant at this time. The results of this study are based on what has been compiled by researchers while researching in the field or at SMA 4 Takalar. The findings collected by researchers namely. (1) The advantages and disadvantages of blended learning where the disadvantages are more dominant than the advantages, because another impact of blended learning is that students cannot focus and get material clearly as in offline learning, and the teacher has difficulty controlling students and cannot assess student assignments. (2) The difficulties or problems encountered are common factors during blended learning (online) students are more constrained by the network and also the internet connection. Meanwhile, during class (offline) students sometimes cannot concentrate on completing assignments given by the teacher. (3) the teacher's solution to improve blended learning in English classes is to develop lesson plans (learning models) that are easily understood by students. The discussion is based on the overall findings that are reinforced by the theory in question. Conclusions and suggestions are divided into 3 according to the constructive problem formulation.